Effect of High Pressure Treatment on Organoleptic and Microbial Quality of Food Products - PIROOZIFARD, MIRKHALIL; ASHRAFI, ROGHIEH; REZAZAD, MAHMOOD; LASHKARI, HANAN; MEHRYAR, LALEH (Asian Journal of Chemistry, 2010)
In recent years high pressure processing has been investigated as an alternative method for food preservation. High pressure technology allows inactivation of microorganisms while maintaining sensory and nutritional properties of foods. The present paper gives an overview of approaches which have been reported in literature about inactivation vegetative bacterial cells, bacterial spores, viruses, algal biotoxin, yeast and moulds, as well as effect of high pressure treatment on colour, flavour and texture of food products.